Técnicas estendidas do contrabaixo em três arranjos crossover de canções populares - Joao Paulo Ferreira Campos (2018)
In the second half of the 20th century, the double bass adapts and absorbs innovative compositional elements of classical music and performance practices of popular music. The present research, of exploratory and creative nature, aims to associating seeks to associate these two languages (classical and popular) by applying extended techniques in the composition of crossover arrangements for chamber double bass, based on a new reading (arrangements) of three consecrated Brazilian popular songs. The study is preceded by a review of treatises on the contemporary double bass and involves six methodological steps: (1) selection and description of extended double bass techniques that can be used in the elaboration of arrangements of traditional Brazilian popular music, as well as presenting a consistent musical notation for such techniques to be used in the (2) creation and description of new extended techniques in double bass, or combination of techniques already known, that translate specific intentions sought in the process of composition and arrangement; (3) selection of three popular Brazilian songs Canto para minha morte [Song for my death], No Morro da Casa Verde [On the Green House Hill] and Metal contra as nuvens [Metal against the clouds] with diversified atmospheres based on the Circumplex Model of Affects (RUSSELL, 1980) adapted to field of music (BORÉM and TAGLIANETTI, 2016); (4) creation of three original arrangements of popular Brazilian songs for chamber bass without accompaniment; (5) the presentation of MaPAs (Performance Audiovisual Maps) and excerpts from EdiPAs (Performance Audiovisual Editions) (BORÉM 2016; 2014) of the three arrangements as pedagogical tool in the teaching of double bass and (6) the presentation of the three arrangements in recital